Antibiotic Prophylaxis for Urinary Tract Infection-Related Renal Scarring: A Systematic Review. - Hewitt, Ian K; Pennesi, Marco; Morello, William; Ronfani, Luca; Montini, Giovanni (Pediatrics, 2017)
CONTEXT: Acute pyelonephritis may result in renal scarring. Recent prospective studies have shown a small benefit of antibiotic prophylaxis in preventing symptomatic and febrile urinary tract infections (UTIs), while being underpowered to detect any influence in prevention of renal damage. OBJECTIVES: Review of the literature and a meta-analysis to evaluate the effect of antibiotic prophylaxis on UTI-related renal scarring. DATA SOURCES: Medline, Embase, and Cochrane Controlled Trials Register electronic databases were searched for studies published in any language and bibliographies of identified prospective randomized controlled trials (RCTs) performed and published between 1946 and August 2016. STUDY SELECTION: Subjects 18 years of age or younger with symptomatic or febrile UTIs, enrolled in prospective RCTs of antibiotic prophylaxis where Tc dimercaptosuccinic acid scans were performed at entry into the study and at late follow-up to detect new scar formation. DATA EXTRACTION: The literature search, study characteristics, inclusion and exclusion criteria, and risk of bias assessment were independently evaluated by 2 authors. RESULTS: Seven RCTs (1427 subjects) were included in the meta-analysis. Our results show no influence of antibiotic prophylaxis in preventing renal scarring (pooled risk ratio, 0.83; 95% confidence interval, 0.55-1.26) as did a subanalysis restricted to those subjects with vesicoureteral reflux (pooled risk ratio, 0.79; 95% confidence interval, 0.51-1.24). LIMITATIONS: Limitations include the small number of studies, short duration of follow-up, and insufficient children with high-grade dilating reflux and/or renal dysplasia enrolled in the studies. CONCLUSIONS: Antibiotic prophylaxis is not indicated for the prevention of renal scarring after a first or second symptomatic or febrile UTI in otherwise healthy children.
Keywords: Acute Disease; Antibiotic Prophylaxis; Child; Cicatrix; Humans; Kidney; Pyelonephritis; Urinary Tract Infections